Fortilin binds CTNNA3 and protects it against phosphorylation, ubiquitination, and proteasomal degradation to guard cells against apoptosis - Mari Nakashima; Decha Pinkaew; Uttariya Pal; Fei Miyao; Hanna Huynh; Lena Tanaka; Ken Fujise (Communications Biology)
Abstract Fortilin, a 172-amino acid polypeptide, is a multifunctional protein that interacts with various protein molecules to regulate their functions. Although fortilin has been shown to interact with cytoskeleton proteins such as tubulin and actin, its interactions with the components of adherens junctions remained unknown. Using co-immunoprecipitation western blot analyses, the proximity ligation assay, microscale thermophoresis, and biolayer interferometry, we here show that fortilin specifically interacts with CTNNA3 (α-T-catenin), but not with CTNNA1, CTNNA2, or CTNNB. The silencing of fortilin using small interfering RNA (siRNAfortilin) promotes the proteasome-mediated degradation of CTNNA3 in 293T cells. Using both fortilin-deficient THP1 cells and 293T cells that overexpress wild-type (WT), phospho-null (5A), and phospho-mimetic (5D) CTNNA3s, we also show that the absence of fortilin accelerates the phosphorylation of CTNNA3, leading to its ubiquitination and proteasome-mediated degradation. Further, the silencing of CTNNA3 using siRNACTNNA3 causes 293T cells to undergo apoptosis. These data suggest that fortilin guards the cells against apoptosis by positively regulating the pro-survival molecule CTNNA3 by protecting it against phosphorylation, ubiquitination, and proteasome-mediated degradation.